Primary culture of fibrocondrocytes from rabbit knee joint meniscus - Figueiredo, Cristina Adelaide (2005)
The present study describes a primary culture of meniscus fibrocartilaginous tissue cultivated in high density technique. Cells were isolated from menisci fibrocartilaginous from 120 days-old New Zealand white rabbits. Menisci were finely minced , and treated with 2mg/mL collagenase in DMEM (Dulbecco's modified Eagle's medium) containing 10% FSC (fetal calf serum) in a shaker for three hours at 37ºC. Fibrochondrocyte cells were seeded at high density (1x105 cells /cm2) in T25 flasks containing DMEM supplemented with 10% FCS. Nearly 80% of cells attached to the flask , and after culturing for five days the cells were uniformly displayed as an elongated, fibroblastic-like morphology. The cells showed confluence after approximately 15 days of culture ,and produced sufficient extracellular matrix which could be evidenced by the appearance of toluidine blue metachromasia. No morphological changes were observed in fibrochondrocytes during cells growing. The fibrochondrocytes cells growth rate increased 2.5 fold, and attained to the stationary phase. During seven days, the newly glycosaminglycans synthesizing cells, the rate of total synthesis of glycosaminglycan was high, and it remained stable after monolayer cells confluency. Ultrastructural morphology of monolayer cells after culturing for eight days was identical to typical fibrochondrocyte in vivo.